An improved deepfake detection using deep learning - Paul, Annay; Dey, Binayak Kumar; Mostafa, Md; Mosfakin, Maharin; Tonika, Rukshana Amin (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.